Design and Fabrication of Hybrid Solar-Biomass System for Crops Drying - Irwan Syah Bin Mohd Yasin, Irwan Syah (Universiti Teknologi Petronas, 2008)
The project is focused on the designing, fabrication, and testing the solar-biomass hybrid system for drying the crops and also analysing its performance. Calculation of heating energy used for drying process of 80% of crop’s moisture content and its thermal efficiency, incident of solar radiation, speed and mass flowrate of air are included in designing process besides the dimension of the hybrid drier unit and the material used.